Human cytomegalovirus inhibits peptide translocation into the endoplasmic reticulum for MHC class I assembly - Hengel, Hartmut; Flohr, Thomas; Hämmerling, Günter J.; Koszinowski, Ulrich; Momburg, Frank (Journal of general virology, 1996)
Human cytomegalovirus (HCMV) genes expressed in the early phase of infection mediate the destabilization of nascent major histocompatibility complex (MHC) class I molecules in infected cells and thus prevent antigen presentation to CD8+ T lymphocytes. We report that HCMV genes interfere with the MHC class I pathway of antigen presentation by at least two mechanisms. Firstly, permissive infection of fibroblasts is characterized by a continuous decline in the capacity to translocate peptides from the cytosol into the endoplasmic reticulum (ER) by the transporter associated with antigen processing (TAP). Inactivation of peptide transport is operative despite augmented TAP expression during HCMV infection. Secondly, TAP molecules fail to associate with MHC class I heavy chains indicating that HCMV early gene expression also interferes with MHC class I maturation. A temperature-sensitive mutant of HCMV, ts9, which lacks 15 kb of DNA encoding the genes US1-US15 of HCMV, had lost the capacity to interfere with MHC class I assembly and to inhibit the peptide translocation function of TAP. One of the genes deleted in ts9, US11, which was reported to downregulate the expression of MHC class I molecules, does not affect peptide transport by TAP. Therefore, we conclude that HCMV encodes at least two early gene functions that interfere with the MHC class I antigen presentation pathway.